cambridge ielts 4 : (Cambridge, 2007)
Cambridge IELTS 4 provides students with an excellent opportunity to familiarise themselves with IELTS and to practise examination techniques using authentic test material from Cambridge ESOL. An introduction to these different modules is included in each book, together with an explanation of the scoring system used by Cambridge ESOL